Comparing Complementary and Alternative Medicine Use with or without Including Prayer as a Modality in a Local and Diverse United States Jurisdiction - Robles, Brenda; Upchurch, Dawn M.; Kuo, Tony (Frontiers in Public Health, 2017)
Objectives: Few studies to date have examined the utilization of complementary and alternative medicine (CAM) in a local, ethnically diverse population in the United States (U.S.). Fewer have addressed the differences in their use based on inclusion or exclusion of prayer as a modality. Variable definitions of CAM are known to affect public health surveillance (i.e., continuous, systematic data collection, analysis, and interpretation) or benchmarking (i.e., identifying and comparing key indicators of health to inform community planning) related to this non-mainstream collection of health and wellness therapies. The present study sought to better understand how including or excluding prayer could affect reporting of CAM use among residents of a large, urban U.S. jurisdiction. Design: Using population-weighted data from a cross-sectional Internet panel survey collected as part of a larger countywide population health survey, the study compared use of CAM based on whether prayer or no prayer was included in its definition. Patterns of CAM use by socio-demographic characteristics were described for the two operationalized definitions. Multivariable binomial regression analyses were performed to control for gender, age, race/ethnicity, education, employment, income, and health insurance status. One of the analyses explored the associations between CAM use and racial/ethnic characteristics in the study sample. Setting: Los Angeles County, California. Subjects: A socio-demographically diverse sample of Los Angeles County residents. Outcome Measures: CAM use (with prayer) and CAM use (excluding prayer). Results: Blacks were among the highest users of CAM when compared to Whites, especially when prayer was included as a CAM modality. Regardless of prayer inclusion, being a woman predicted higher use of CAM. Conclusions: How CAM is defined matters in gauging the utilization of this non-mainstream collection of therapies. Given that surveillance and/or benchmarking data are often used to inform resource allocation and planning decisions, results from the present study suggest that when prayer is included as part of the CAM definition, utilization/volume estimates of its use increased correspondingly, especially among non-White residents of the region.